2018
DOI: 10.1159/000486584
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion in Preterm Infants: Current Evidence and Controversies

Abstract: The current evidence regarding the indication, advantages and risks of red blood cell transfusion (RBCT) for preterm infants is discussed. This is an important area in Neonatology to be examined given that 90% of extremely low birth weight infants receive RBCT and many controversies remain regarding when to transfuse and the risks of RBCT. The various treatment thresholds and guidelines used are presented and we compare the short-term clinical benefits of liberal and restrictive RBCT in preterm infants; the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
119
1
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 78 publications
1
119
1
15
Order By: Relevance
“…Randomised trials comparing targeting more restrictive versus more liberal Hb concentrations (about 1–2 g/dL lower) result in reduced need for blood transfusion without affecting hospital outcomes, and recent British Committee for Standards in Haematology based their thresholds on these more restrictive thresholds [184]. However post hoc analysis of long-term follow-up data from one study showed some better cognitive outcomes in those with more liberal Hb thresholds highlighting the need for further studies in this area [185, 186]. It remains unclear whether a liberal or restrictive transfusion policy is best.…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…Randomised trials comparing targeting more restrictive versus more liberal Hb concentrations (about 1–2 g/dL lower) result in reduced need for blood transfusion without affecting hospital outcomes, and recent British Committee for Standards in Haematology based their thresholds on these more restrictive thresholds [184]. However post hoc analysis of long-term follow-up data from one study showed some better cognitive outcomes in those with more liberal Hb thresholds highlighting the need for further studies in this area [185, 186]. It remains unclear whether a liberal or restrictive transfusion policy is best.…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…At least 40% of very low‐birth‐weight infants (<1500 g at birth) and about 90% of extremely low‐birth‐weight infants (<1000 g at birth) require at least one RBC transfusion during their hospitalization, related to phlebotomy losses and an exaggerated postnatal nadir of anemia . Exposure to prolonged anemia may have detrimental consequences on the preterm infant, contributing to complications related to prematurity and poor growth . Conversely, RBC transfusions are not without risks, including potential associations with necrotizing enterocolitis, bronchopulmonary dysplasia, retinopathy of prematurity, intraventricular hemorrhage, and adverse long‐term neurodevelopmental outcomes .…”
mentioning
confidence: 99%
“…Additionally, preterm infants with anemia extract more oxygen compared to non‐anemic preterm infants . Research delineating Hct threshold for optimal improvement in oxygen extraction following RBC transfusion is needed . In this study, we seek to determine the impact of feeding and anemia status on cerebral and mesenteric oxygenation and oxygen extraction response to RBC transfusion in preterm infants.…”
mentioning
confidence: 99%
“…Preterm neonates account for the highest transfusion rate and are the most challenging to determine the risk benefit ratio of blood transfusion. Expert opinion favoring a more liberal approach in preterm neonates, suggests that liberal transfusion thresholds may favor improved neurodevelopmental outcomes . Until safety can be concluded by recent ongoing trials (clinical trials.gov NCT01702805 and NCT01393496) the indications for red cell transfusion in the premature and low birth weight neonate remain challenging.…”
Section: Standard 13 Guidence Patient Blood Management For Pediatricmentioning
confidence: 99%
“…Initial laboratory testing may be performed on a cord blood sample as one strategy to decrease phlebotomy blood losses. Red blood cell transfusions when indicated should be single donor, leukocyte depleted, irradiated and fresh …”
Section: Standard 13 Guidence Patient Blood Management For Pediatricmentioning
confidence: 99%